Prophetic Leadership In Tabligh Aspect: A Study Of Leadership Practices In Darussyifa Al-Fitroh Yaspida’s Business Units - Hanafiah Hanafiah; Lidiawati Lidiawati; Indri Lastriyani; Ida Farida Fitriyani (International Journal of Nusantara Islam, 2023)
This study endeavors to comprehensively elucidate the prophetic leadership style exhibited by the leaders of Pondok Pesantren Darussyifa Al Fitroh Yaspida in Kabupaten Sukabumi, with a specific focus on the Tabligh aspect pertaining to the autonomy of their business units. Employing a qualitative approach with a case study design, the research utilizes data collection techniques involving meticulous observation, in-depth interviews, and diligent documentation. Rigorous data analysis processes encompass data condensation, meticulous data presentation, and astute drawing of conclusions. Data validity is ensured through the judicious application of data triangulation and informant review. The research findings unveil a praiseworthy and well-executed implementation of the seven key indicators of prophetic leadership in the Tabligh aspect, encompassing: (1) the articulation of a clear and compelling vision, (2) the collaborative sharing of mission and objectives, (3) the adeptness in effective communication, (4) the exemplary leadership by setting a compelling example, (5) the remarkable ability to motivate and inspire, (6) the manifestation of genuine care and compassion, and (7) the adeptness in fostering teamwork. These indicators have been meticulously integrated into the operational framework of the business units within Pondok Pesantren Darussyifa Alfitroh Yaspida. This research substantiates the remarkable effectiveness of prophetic leadership within Pondok Pesantren Darussyifa Al Fitroh Yaspida, particularly in the Tabligh aspect. The thorough exploration of leadership practices and their seamless integration within the business units reflects the profundity of their commitment to fostering a harmonious and spiritually enriched working environment, ultimately contributing to the success and prosperity of the institution